Nintedanib and Dasatinib Treatments Induce Protective Autophagy as a Potential Resistance Mechanism in MPM Cells - Hegedüs, Luca; Szücs, Kata D.; Kudla, Matthias; Heidenreich, Julian; Jendrossek, Verena; Peña-Llopis, Samuel; Garay, Tamas; Czirok, Andras; Aigner, Clemens; Plönes, Till; Vega-Rubin-de-Celis, Silvia; Hegedüs, Balazs (Frontiers in Cell and Developmental Biology, 2022)
Malignant pleural mesothelioma (MPM) is a rare type of cancer with a grim prognosis. So far, no targetable oncogenic mutation was identified in MPM and biomarkers with predictive value toward drug sensitivity or resistance are also lacking. Nintedanib (BIBF1120) is a small-molecule tyrosine kinase inhibitor that showed promising efficacy preclinically and in phase II trial in MPM as an angiogenesis inhibitor combined with chemotherapy. However, the extended phase III trial failed. In this study, we investigated the effect of nintedanib on one of its targets, the SRC kinase, in two commercial and six novel MPM cell lines. Surprisingly, nintedanib treatment did not inhibit SRC activation in MPM cells and even increased phosphorylation of SRC in several cell lines. Combination treatment with the SRC inhibitor dasatinib could reverse this effect in all cell lines, however, the cellular response was dependent on the drug sensitivity of the cells. In two cell lines, with high sensitivity to both nintedanib and dasatinib, the drug combination had no synergistic effect but cell death was initiated. In two cell lines insensitive to nintedanib combination treatment reduced cell viability synergisticaly without cell death. In contrast, in these cells both treatments increased the autophagic flux assessed by degradation of the autophagy substrate p62 and increased presence LC3B-II, increased number of GFP-LC3 puncta and decreased readings of the HiBiT-LC3 reporter. Additionaly, autophagy was synergistically promoted by the combined treatment. At the transcriptional level, analysis of lysosomal biogenesis regulator Transcription Factor EB (TFEB) showed that in all cell lines treated with nintedanib and to a lesser extent, with dasatinib, it became dephosphorylated and accumulated in the nucleus. Interestingly, the expression of certain TFEB target genes implicated in autophagy or lysosomal biogenesis were significantly modified only in one cell line. Finally, we showed autophagy induction in our MPM cell lines panel by nintedanib and dasatinib is independent of the AKT/mTOR and the ERK pathways. Our study reveals that autophagy can serve as a cytoprotective mechanism following nintedanib or dasatinib treatments in MPM cells.